The feasibility of Passive Downdraught Evaporative Cooling (PDEC) of multi-storey office buildings in Cairo - a modelling study - Ibraheem, Omar (2018)
Climatic stress on buildings in hot-dry climates has long been negotiated by means of evaporative cooling, the origins of which could be traced back to Egypt and the Middle East. However, this millennia-old strategy needs to undergo much scrutiny in its design and implementation to meet the requirements of contemporary comfort standards for offices. The task is even more onerous if multi-storey buildings are considered. Acknowledging Cairo to be one of the most densely populated cities in the world and in light of the growing demand on high quality office space in recent years, it is anticipated that extending the application of evaporative cooling to medium and high-rise office buildings is imperative if this strategy is to be widely adopted as an alternative to conventional air-conditioning in Cairo given that existing research and applications are limited to low-rise buildings. This work proposes a four-stage plan to achieve that. The first stage entails the development of a generic prototype of the Passive Downdraught Evaporatively Cooled (PDEC) multi-storey office building that allows three distinct airflow patterns and two modes of operation to take place. The second stage makes use of analytic models for the initial sizing of the airflow components. The third stage assesses the performance of a base case model of the generic PDEC building in terms of bulk airflow rates, airflow distribution across the floors, internal thermal conditions, and relevant environmental costs using EnergyPlus, the whole building dynamic thermal simulation program with integrated airflow network modelling. The fourth and final stage is that of optimisation wherein the effects of varying a number of parameters on performance are established. The study shows that in comparison to free-running naturally-ventilated buildings, and depending on the thermal comfort model adopted, PDEC can potentially deliver comfort conditions for all occupied hours of the cooling season in Cairo. Buoyancy ‘stack’ forces alone generated by temperature differences can drive sufficient airflow rates without wind assistance, a scenario that is likely to occur in dense urban contexts. The study demonstrates the effectiveness’ of dividing multi-storey buildings into isolated segments in terms of airflow (segmentation) and the benefits of extending PDEC operation beyond occupied hours. Changes in wind direction and speed were also considered and have shown to be of less significance if air inlets and outlets are properly located. Fine tuning of the building management system and adopting a more relaxed overheating criterion are key factors in limiting the increase in daily water consumption due to PDEC in light of the diminishing availability of sustainable water resources in the region. This study is the first to provide an understanding of how multi-storey office buildings in hot-dry climates can be designed and operated to incorporate PDEC as a viable alternative to AC. The novelty here lies not in the methodology which uses available models, but in the detailed investigation of flow rates, flow patterns, indoor temperatures, and water consumption.